Effect of waste oyster shell powder on the properties of alkali-activated slag–waste ceramic geopolymers - Gui-Yu Zhang; Run-Sheng Lin; Xiao-Yong Wang (Journal of Materials Research and Technology, 2023)
The ceramic and oyster farming industries produce large amounts of waste ceramics and oyster shells. Meanwhile, alkali-activated materials are less environmentally impacted materials with the potential to replace Portland cement. Adding ceramic powder (CP) and waste oyster shell powder (WOS) to alkali-activated materials can relieve the pressure on landfills and protect the environment, thereby having important implications. This study aims to add WOS to alkali-activated adhesives and investigate their effects on the properties of the samples. The blast furnace slag and ceramic powder were partially replaced by 0–20 wt% WOS. The specimens for control, 10% WOS, and 20% WOS are named as WOS-0, WOS-10, and WOS-20, respectively. Experimental studies on the compressive strength testing, heat of hydration, ultrasonic pulse velocity (UPV), thermogravimetric (TG) analysis, Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and electrical resistance rate were performed. The experimental results are as follows: (1) An increase in the WOS substitution rate increased the hydration heat release rate and decreased the compressive strength. At 3 days of age, the compressive strength of the WOS-20 sample decreased by 4.3 MPa compared with the WOS-0 sample. (2) UPV and resistivity decreased with increasing WOS substitution. At 3 days of age, the UPV of the WOS-20 sample decreased by 0.11 km/s compared with the WOS-0 sample. (3) The TG results showed that WOS participated in the alkali-activated reaction. For the WOS-20 sample, the amount of calcium carbonate decreased by 2.9% as the age increased from 3 days to 28 days. (4) XRD and FT-IR spectra showed the intensified carbonate peak with the increase in the WOS content. These findings suggest that CP and WOS can be used as complementary gelling agents for alkali-activated materials.